(untitled) (Minerva, 2022)
This paper offers a comprehensive analysis of a physic interpretation of the myth of Ares and Aphrodite narrated in the Odyssey. Such an interpretation dates back to the Komnenos period and is compiled in Allegoriae Odysseae by the Byzantine intellectual John Tzetzes (1110-1180). The paper aims to examine the intertextualities both with other works by the same author as well as with other interpreters. The paper will also focus on the cosmological conception, some aspects pertaining to gender roles, the new treatment of the gods, as well as the style. By doing so, the intention is to show how the Homeric subject was reworked in the Byzantine era.